Knowledge, Attitudes, and Usage of Apitherapy for Disease Prevention and Treatment among Undergraduate Pharmacy Students in Lithuania. (30th November 2015) - Trumbeckaite, Sonata; Dauksiene, Jurgita; Bernatoniene, Jurga; Janulis, Valdimaras
Abstract : Traditional medicine therapies are historically used worldwide for disease prevention and treatment purposes. Apitherapy is part of the traditional medicine based on bee product use. Complementary medicine practices which incorporate use of some traditional herbal, mineral, or animal kind substances very often are discussed with pharmacy professionals because these products are often sold in pharmacies as dietary supplements. This study is aimed at determining the attitude, knowledge, and practices of apitherapy among undergraduated pharmacy students (Master of Pharmacy) who already have a pharmacy technician diploma and from 1 to 20 years of practice working in a community pharmacy as pharmacy assistants. A method of questionnaire was chosen. The questions about attitudes, experience, knowledge, and practices for disease prevention and treatment of different bee products, their safety, and informational sources were included. Respondents shared opinion that use of bee product is part of the traditional medicine. Most of them had experience on honey product use for treatment and disease prevention for themselves and their family members (62%) although the need of more evidence based information was expressed. The most known bee products were honey, propolis, and royal jelly. They are widely used for enhancing the immune system and prevention of respiratory tract infection.